Built to change; revitalizing a spoilded place - Lam, Zoe Timon Niklas (My University, 2025)
This masters thesis investigated how architecture can help revitalizing environmental damaged sites by carefully integrating the existing structure into the design. By in depth analysis of the site and its genius loci, the site has been adapted to the new functions needs as a fundamental socializing area and strengthened in its relationship with the surrounding nature. The study focused on a waste management site on Öckerö Island, Goth - enburg, that will soon be abandoned and therefore, due to sustainability reasons and expansion visions of the municipality, needs a new purpose. With the aim to transform a environmentally and aesthetically spoiled place into a meaningful public space, that supports the local municipalities goals for a strong maritime heritage and residents engagement, especially for younger generations and rough weather times. The research methodology included various site visits and analysis and is mainly conducted by classical architectural sketching, drawings, 3D mod - elling and physical model building to test design strategies. With the special emphasis on existing structures and the surrounding landscapes, architecture was used as a space making tool and not only to create indoor facilities. The intervention therefore had the goal to enhance the existing structures and its immediate surrounding by careful choice of placement, tectonics and material. The results showed that, at the current state, undesired structures could be revitalised due to architectural interventions which concentrate on finding spacial experiences with the site. Strategically placed walls in various heights and two building typologies helped the place to become an asset for the community and travellers seeking shelter in bad weather times while emphasizing on the beautiful nature and the places history. The conclusion highlighted that the design methodology enabled the place in various ways, but also imposed significant constraints, narrowing the range of design possibilities by adjusting heavily onto the landscape and landscape. Therefore the design rooted strongly into the historical and natural context but resulted in solutions which size and material was mainly driven by the place. The result of a theoretical thesis is the lack of a client, which might differ from the exact needs of municipality and its financial capabilities.
Keywords: architectural revitalisation, contextual architecture, landscape architecture, genius loci, bathhouse, restaurant